The Effectiveness of Using Kahoot! Application as An Evaluation Tool in Arabic Vocabulary Learning at Madrasah Ibtidaiyah - Irma Nur Fiani; Mohammad Ahsanuddin; Romyi Morhi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Kahoot application in learning can also help teachers to collect feedback from students, assess students’ learning understanding, and make surveys about problems that can be identified during learning. This research aimed to describe the effectiveness of using Kahoot! application as an evaluation tool in Arabic vocabulary learning for fifth-grade students at MI Al-Ma’arif 01 Margomulyo, Blitar. This research was qualitative with a One Group Pretest Posttest design – an experiment carried out in one group only without comparison. The samples of this research were the fifth-grade 25 students of MI Al-Ma'arif 01 Margomulyo Blitar. The results showed that the average evaluation score of the students after using Kahoot! application as a learning media increased by 75.2, much higher than before, it was 37.6. The use of Kahoot! application as an evaluation tool in Arabic vocabulary learning contributed 32% to the learning outcomes of the fifth-grade students at MI Al-Ma'arif 01 Margomulyo.